The Relationship between Wrist Flexibility and the Ability to Hit Dropshot Badminton Players - Akkase, Arfandi (Journal Physical Health Recreation (JPHR), 2025)
This study discusses the relationship between wrist flexibility and badminton players' Dropshot ability. 15 badminton players at PB Manisa Sidrap were involved in this study and selected using total sampling technique. Data analysis used Pearson product moment correlation analysis. The results of the correlation test showed that there was a relationship between wrist flexibility and badminton players' Dropshot ability with a significance value of 0.002 <0.05. The direction of the relationship produced a positive correlation with a value of 0.224 which indicates that the strength of the relationship between wrist flexibility and badminton players' Dropshot ability is in the range of 0.200-0.399 which means that the strength of the relationship is weak.